2022
DOI: 10.1186/s12913-022-08796-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of the knowledge to action model improved physical therapist adherence to a common clinical practice guideline across multiple settings: a multisite case series

Abstract: Background When a new guideline is published  there is a need to understand how its recommendations can best be implemented in real-world practice. Yet, guidelines are often published with little to no roadmap for organizations to follow to promote adherence to their recommendations. The purpose of this study was to evaluate the impact of using a common process model to implement a single clinical practice guideline across multiple physical therapy clinical settings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Health care KT research suggests that using multiple active KT strategies where participants engage in both learning and behavior change activities is most effective. 42,43 Using KT frameworks to formally identify barriers to and facilitators of change provides a lens for understanding, addressing, and explaining complex variables across multiple organizational levels. Compared with informal strategies such as staff meetings and perceived barriers, theory-informed formal assessment of the context in which clinicians negotiate the desired practice change allows for more specific selection and mapping of KT strategies to barriers.…”
Section: Phases and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Health care KT research suggests that using multiple active KT strategies where participants engage in both learning and behavior change activities is most effective. 42,43 Using KT frameworks to formally identify barriers to and facilitators of change provides a lens for understanding, addressing, and explaining complex variables across multiple organizational levels. Compared with informal strategies such as staff meetings and perceived barriers, theory-informed formal assessment of the context in which clinicians negotiate the desired practice change allows for more specific selection and mapping of KT strategies to barriers.…”
Section: Phases and Outcomesmentioning
confidence: 99%
“…Health care KT research suggests that using multiple active KT strategies where participants engage in both learning and behavior change activities is most effective 42,43. Using KT frameworks to formally identify barriers to and facilitators of change provides a lens for understanding, addressing, and explaining complex variables across multiple organizational levels.…”
Section: Phases and Outcomesmentioning
confidence: 99%
“…One recent study found that utilization of neck and low back CPGs was about 70%; however, utilization was not associated with final pain or disability in the study cohort [4]. A great deal of interest in the literature is focused on utilization of other clinical practice guidelines [5][6][7][8]. Much of the current data focuses on adherence to other CPGs, such as for low back pain or concussion [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This is possibly one of the first studies to explore implementation process models in detail to determine common features and constructs. The KTA framework has been applied to several clinical guideline implementation studies (223,(225)(226)(227)229,230,248) and it is recommended by established respiratory societies that have a broad membership (222,238). Researchers that have applied the framework propose tailoring implementation and strategies to the local context.…”
Section: Strengthsmentioning
confidence: 99%
“…et al,(230) applied the KTA framework to implement newly published physical therapy guidelines for patients with peripheral vestibular hypofunction across five clinical sites in the US with established rehabilitation services. To determine the impact of implementation the researchers conducted preliminary gap surveys and meetings to determine the target behaviours that would be critical to improving guideline adherence before assessing behaviour change 6months after guideline implementation.…”
mentioning
confidence: 99%